Öt történet . Five Stories (Menedék Egyesület, 2011)
Five short documentaries about immigrants living in Hungary. Day Off by Krisztián Marton; Ayanbele by Péter Szabó; Botz by Dávid Szőnyei and Zsófi Lili Kovács; Exam by Veronika Gaszner; It’s Tastier Eating with Hands by Fanni Hatházi.